Leukaemic hypopyon in acute lymphoblastic leukaemia after interruption of treatment. Issue 1 (January 1979) - Masera, G; Carnelli, V; Uderzo, C; Toselli, C; Lasagni, F; Lambertenghi, E
Abstract : A 7-year-old girl was successfully treated for acute lymphoblastic leukaemia, and remained in remission after treatment had been completed in 3 years. Four months after cessation of treatment, iridocyclitis with hypopyon developed in one eye. Exudate from the anterior chamber contained numerous lymphoblasts. Local radiotherapy led to complete resolution of the ocular lesions, and the patient remains well 22 months later.